Statistical survey of nighttime midlatitude magnetic fluctuations: Their source location and Poynting flux as derived from the Swarm constellation. Issue 11 (5th November 2016) - Park, Jaeheung; Lühr, Hermann; Stolle, Claudia; Rodriguez‐Zuluaga, Juan; Knudsen, David J.; Burchill, Johnathan K.; Kwak, Young‐Sil
Abstract: This is the first statistical survey of field fluctuations related with medium‐scale traveling ionospheric disturbances (MSTIDs), which considers magnetic field, electric field, and plasma density variations at the same time. Midlatitude electric fluctuations (MEFs) and midlatitude magnetic fluctuations (MMFs) observed in the nighttime topside ionosphere have generally been attributed to MSTIDs. Although the topic has been studied for several decades, statistical studies of the Poynting flux related with MEF/MMF/MSTID have not yet been conducted. In this study we make use of electric/magnetic field and plasma density observations by the European Space Agency's Swarm constellation to address the statistical behavior of the Poynting flux. We have found that (1) the Poynting flux is directed mainly from the summer to winter hemisphere, (2) its magnitude is larger before midnight than thereafter, and (3) the magnitude is not well correlated with fluctuation level of in situ plasma density. These results are discussed in the context of previous studies. Key Points: During solstices the MMF Poynting flux is preferentially (but not always) from summer to winter hemisphere Magnitudes of the MMF Poynting flux peak around 2000‐2100 MLT and are larger before midnight than after The magnitudes of the MMF Poynting flux is not well correlated with the undulation levels of in situ plasma density